Clinical and Laboratory Analysis of the Efficiency of Hirudotherapy in Complex Treatment of Endodontal Diseases - Andrei Sevbitov (Journal of Global Pharma Technology, 2016)
To date, teeth with inflammation in the periapical tissues, including destructive ones, often give non-abating exacerbations by conservative treatment, and they are removed. The article displays the clinical and laboratory results of a study of the effectiveness of hirudotherapy in combination therapy of inflammatory diseases of the endodontic. In recent years, a number of new drugs and methods for the treatment of chronic apical periodontitis have been proposed. The arsenal of new drugs for endodontic practice is extensive, but the result of treatment is often not optimistic. The purpose of the study was to conduct a clinical and laboratory analysis of the method of hirudotherapy to increase the effectiveness of treatment of chronic apical periodontitis. Based on clinical and laboratory data, the local course of the inflammatory process was studied, including cases when using hirudotherapy in patients with acute exacerbation of chronic apical periodontitis. Hirudotherapy allows one to stop inflammatory syndrome in earlier periods and reduce the time of treatment. The use of hirudotherapy in the combination with conventional endo therapy of patients with chronic apical periodontitis result in pronounced anti-inflammatory, analgesic, and vasoconstrictor effect that increases the effectiveness of treatment of chronic apical periodontitis.Keywords: Inflammation, Apical periodontitis, Hirudotherapy, Cytomorphology, Protocooperation.